Systematic review of adherence rates by medication class in type 2 diabetes: a study protocol. Issue 2 (29th February 2016) - McGovern, Andrew; Tippu, Zayd; Hinton, William; Munro, Neil; Whyte, Martin; de Lusignan, Simon
Abstract : Introduction: Treatment options for type 2 diabetes are becoming increasingly complex with people often prescribed multiple medications, and may include both oral and injectable therapies. There is ongoing debate about which drug classes provide the optimum second-line and third-line treatment options. In the real world, patient adherence and persistence determines medication effectiveness. A better understanding of adherence may help inform the choice of second-line and third-line drug classes. Methods and analysis: This systematic review will compare adherence and persistence rates across the different classes of medication available to people with type 2 diabetes. It will include all identified studies comparing medication adherence or persistence between two or more glucose-lowering medications in people with type 2 diabetes. Research databases (MEDLINE, EMBASE, The Cochrane Library, The Register of Controlled Trials, PsychINFO and CINAHL) will be searched for relevant articles, using a comprehensive search strategy. All identified medication trials and observational studies will be included which compare adherence or persistence across classes of diabetes medication. The characteristics and outcomes of all the included studies will be reported along with a study quality grade, assessed using the Cochrane Risk Assessment Tool. The quality of adjustment for confounders of adherence or persistence will be reported for each study. Where multiple (n ≥3) studies provide compare adherence or persistence across the same 2 medication classes, a meta-analysis will be performed. Ethics and dissemination: No ethics approval is required. This review and meta-analysis (where possible) will provide important information on the relative patient adherence and persistence, with the different classes of diabetes therapies. Once complete, the results will be made available by peer-reviewed publication. Trial registration number: CRD42015027865.